PENGARUH KOMPETENSI GURU PAI TERHADAP KARAKTER SISWA MI AL HIJRAH KOTA MAKASSAR - Musbaing; Erniati (Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Makassar, 2019)
Abstract: The Effect of PAI Teacher Competence on the Students’ Characters of MI Al Hijrah in Makassar City. This study aimed to determine the competence of PAI teachers and the students’ character of MI Al Hijrah Makassar, and whether the competence of PAI teachers had positive effect on the students’ character of MI Al Hijrah Makassar. This type of research was correlational research (ex-post facto). This research variable consisted of two variables, namely the competence of PAI teachers with the symbol X, and students’ characters with the symbol Y as the independent variable. The population of this research was all MI Al Hijrah Makassar students. Sampling technique used cluster random sampling. All students became research respondents, namely 32 students. The research instrument used in this research was questionnaire. Data collected from this research were processed using descriptive statistics and inferential statistics using simple regression or conversion formulas. The results obtained by the competence of PAI teachers were in the average category with the mean score of 186.09 from the ideal score of 297 with the standard deviation of 47,062 and the variance of 2214,797. The students’ characters variable of MI Al Hijrah Makassar City was in the low category with the average score of 37.91 from the ideal score of 100 with the standard deviation of 19.451 and the variance of 378,346. Based on the results of inferential statistical analysis obtained the positive effect of PAI teacher competence on the students’ character of MI Al Hijrah Makassar, at the significance level of 0.05, with the coefficient of determination (R2) of 25.5%.